SISTEM INFORMASI DOKUMEN PENDUKUNG UJIAN AKHIR SEMESTER - Muhammad Najibulloh Muzaki; M. Dewi Manikta Puspitasari; Rini Indriati (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
The final semester examination is a routine agenda for each semester for the Program Studi Sistem Informasi Universitas Nusantara PGRI Kediri. In the implementation of the final semester exams, some of the supporting documents are the exam schedule, minutes of the exam and the list of attendees of the exam. In the minutes of the exam and the attendance list, some entries must be written by the supervisor. Some of the fields include data on day, date, exam time, exam room, course name, lecturer, class and supervisor's name. Each of these documents is made in 2 copies, so that the filling process can take up the time of the supervisor when carrying out supervisory duties. When examined, some of the entries are actually already in the exam schedule, just how to make the data contained in the schedule can be integrated to complete the fields. This problem exists because there is no system or database that is the basis for making these documents. This study aims to provide a solution by building an information system that helps produce final semester exam support documents, such as exam schedules, minutes of the exam and attendance list of participants, using the PHP programming language and MySQL database support so that the process of making these documents is done systematic and automatic system. The results of the study indicate that with the Information System Supporting the Semeste Final Examination Document, the making of documents can be done in an integrated manner, so that some of the entries no longer need to be handwritten anymore. In the end, the documents produced by the system can save writing time faster.